2022
DOI: 10.1155/2022/3945195
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol-Preconditioned Mesenchymal Stem Cell-Derived Extracellular Vesicles Promote Antioxidant Capacity of Tendon Stem Cells In Vitro and In Vivo

Abstract: Tendon stem cells (TSCs) are often exposed to oxidative stress at tendon injury sites, which impairs their physiological effect as well as therapeutic application. Recently, extracellular vesicles (EVs) derived from bone marrow mesenchymal stem cells (BMSCs) were shown to mediate cell protection and survival under stress conditions. The function of BMSC-EVs may be affected by pretreatment with various factors such as eugenol (EUG)—a powerful antioxidant. In our previous study, we found that H2O2 significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 60 publications
1
45
0
Order By: Relevance
“…Intriguingly, similar to previous reports, , we found that the BMSC-EVs could protect tenocytes from ROS attack and shared similar therapeutic effects with ENs. Furthermore, the ENEVs presented efficient synergic results contributed by both ENs and EVs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Intriguingly, similar to previous reports, , we found that the BMSC-EVs could protect tenocytes from ROS attack and shared similar therapeutic effects with ENs. Furthermore, the ENEVs presented efficient synergic results contributed by both ENs and EVs.…”
Section: Resultssupporting
confidence: 91%
“…Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) are small-sized (50–1000 nm) phospholipid bilayer membranous vesicles that contain protein and nucleic acid released from the host MSCs . Among them, bone marrow stem cell-derived EVs (BMSC-EVs) have been extensively adopted in musculoskeletal tissue regeneration. , Numerous studies have shown that administering BMSC-EVs can promote tendon healing through regulation of the immune microenvironments and improvement of collagen synthesis and tenogenic expression. , Although the BMSC-EVs can inhibit the polarization of M1φ and increase the expression of anti-inflammatory mediators at the early phase of tendon healing, their anti-ROS capacity is very limited and needs to be significantly improved for resolving the accumulation of ROS. , Moreover, the effects of BMSC-EVs on the expression of COLIII vary between studies, , and an antiadhesion effect of native BMSC-EVs has yet to be reported. Recent studies revealed that Zn 2+ could promote tenocyte accumulation, proliferation, and COLI synthesis but inhibit COLIII deposition, thereby making this an effective component in tendon matrix reconstruction. , …”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, hydrogen peroxide (H 2 O 2 ) could simulate an oxidative stress environment, suppress the proliferation and tenogenic differentiation of TDSCs. [ 36 , 37 ] Here, we used CeNPs with ROS scavenging capabilities to explore whether they could reduce the inhibitory effects of H 2 O 2 on the tenogenic differentiation potential of TDSCs. The fresh medium culture alone served as the control group (Ctrl group).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis of adult and fetal tendons after injury showed that there was a significant up-regulation of oxidative stress, pro-inflammatory factors, matrix degrading enzymes and activation of neutrophils in the adult tendon defects, which were not observed in fetal tendon healing, supporting the association of oxidative stress and inflammation with poor healing outcome in adult tendon healing [ 19 ]. The ROS level was shown to increase significantly in the injured tendon, compared to the normal tendon in a rat patellar tendon window injury model [ 20 ]. In addition to acute tendon injury, oxidative stress and inflammation are also associated with tendinopathy.…”
Section: Clinical and Pre-clinical Evidence Of Potential Sources And ...mentioning
confidence: 99%
“…Extracellular-vesicles-derived bone marrow stromal cells (BMSCs) pretreated with eugenol were shown to inhibit ROS accumulation and apoptosis as well as promoting catalase and SOD1 expression, viability, proliferation, and tenogenic differentiation of H 2 O 2 -treated TDSCs, compared to the untreated BMSC-EV group via the Nrf2/HO-1 pathway [ 20 ]. The transplantation of eugenol-BMSC-EV-pretreated TDSCs showed significantly improved tenogenesis and matrix regeneration compared to the untreated TDSCs during tendon healing [ 20 ]. The mechanism, including the anti-oxidative effect, of eugenol-BMSC-EV-pretreated TDSC was not examined in the animal model.…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%